Cyclin A2 regulates erythrocyte morphology and numbers. Issue 22 (16th November 2016) - Jayapal, Senthil Raja; Ang, Heather Yin-Kuan; Wang, Chelsia Qiuxia; Bisteau, Xavier; Caldez, Matias J.; Xuan, Gan Xiao; Yu, Weimiao; Tergaonkar, Vinay; Osato, Motomi; Lim, Bing; Kaldis, Philipp
ABSTRACT: Cyclin A2 is an essential gene for development and in haematopoietic stem cells and therefore its functions in definitive erythropoiesis have not been investigated. We have ablated cyclin A2 in committed erythroid progenitors in vivo using erythropoietin receptor promoter-driven Cre, which revealed its critical role in regulating erythrocyte morphology and numbers. Erythroid-specific cyclin A2 knockout mice are viable but displayed increased mean erythrocyte volume and reduced erythrocyte counts, as well as increased frequency of erythrocytes containing Howell-Jolly bodies. Erythroblasts lacking cyclin A2 displayed defective enucleation, resulting in reduced production of enucleated erythrocytes and increased frequencies of erythrocytes containing nuclear remnants. Deletion of the Cdk inhibitor p27 Kip1 but not Cdk2, ameliorated the erythroid defects resulting from deficiency of cyclin A2, confirming the critical role of cyclin A2/Cdk activity in erythroid development. Loss of cyclin A2 in bone marrow cells in semisolid culture prevented the formation of BFU-E but not CFU-E colonies, uncovering its essential role in BFU-E function. Our data unveils the critical functions of cyclin A2 in regulating mammalian erythropoiesis.